Implementation of HLA-B*15:02 Genotyping as Standard-of-Care for Reducing Carbamazepine/Oxcarbazepine Induced Cutaneous Adverse Drug Reactions in Thailand - Tiwattanon, Kanyawan; John, Shobana; Koomdee, Napatrupron; Jinda, Pimonpan; Rachanakul, Jiratha; Jantararoungtong, Thawinee; Nuntharadthanaphong, Nutthan; Kloypan, Chiraphat; Biswas, Mohitosh; Boongird, Apisit; Sukasem, Chonlaphat (Frontiers in Pharmacology, 2022)
Abstract Objective: This study aimed to investigate the clinical impact of HLA-B*15:02 pharmacogenomics (PGx) testing before carbamazepine (CBZ)/oxcarbazepine (OXC) prescriptions and determine whether these PGx testing were associated with the reduction of CBZ/OXC-induced cutaneous adverse drug reactions (CADRs) in Thailand. Methods: A retrospective observational cohort study was conducted by obtaining relevant HLA-B*15:02 PGx-testing and clinical data from electronic medical records during 2011- 2020. To analyze and summarize the results, descriptive statistics were employed, and Fisher exact was used to compare the clinical difference between the HLA-B*15:02 positive and negative groups. Results: Only 384 patients met the inclusion criteria out of 1,020 patients with HLA genotyping information. Overall, the number of HLA-B*15:02 has been rising year after year, particularly since the national policy screening was implemented in Thailand. Physicians in the majority of cases (85%) requested and waited for PGx reports before prescription, however CBZ/OXC was treated in some emergency cases (15%). Nevertheless there were no CADRs in the HLA-B*15:02 positive group, CBZ-induced SCARs (n=12) were reported in patients who received CBZ without PGx testing. Levetiracetam, sodium valproate, lamotrigine, gabapentin, and phenytoin were the most prescribed as alternative antiepileptic drugs (AEDs) in HLA-B*15:02 carriers. Interestingly, 21 patients got CADRs including mild rash (n=19), early Drug reaction with eosinophilia and systemic symptoms (DRESS, n=1) and Stevens-Johnson syndrome (SJS, n=1) after treated with CBZ/OXC in the HLA-B*15:02 negative (negative group, n=189). Conclusions HLA-B pharmacogenetics testing influenced the selection of appropriate AEDs. The presence of mild rash in the HLA-B*15:02 negative group indicates that other genetic biomarker (HLA-A*31:01) and/or non-genetic variables are involved in CBZ/OXC-induced CADRs, emphasizing that CBZ/OXC prescriptions necessitate CADR monitoring. The hospital policy and clinical decision support (CDS) alert system is essential to overcome the barriers associated with the utilization of PGx guidelines into clinical practice.